Studying of characteristic of GEM40P4 HPGE detector by experiment - Loat, Bui Van; Quan, Nguyen Van; Anh, Le Tuan; Anh, Tran The; Nghia, Nguyen The; Hung, Nguyen Van (VNU Journal of Science: Mathematics - Physics; Vol 25 No 4, 2009)
Abstract